Cross-Cultural Comparison of Self-Construal and Well-Being between Japan and South Korea: The Role of Self-Focused and Other-Focused Relational Selves - Park, Joonha; Norasakkunkit, Vinai; Kashima, Yoshi (Frontiers in Psychology, 2017)
Relational self, along with individual and collective selves, is a fundamental aspect that makes up self-concept. Proposing its two aspects: self-focused relational self (i.e., perceiving the self as the object of other people’s referential awareness or intentionality) and other-focused relational self (i.e., perceiving the self as being attuned and empathetically connected to close others), the current study explored the way the four selves affect well-being in Japan and South Korea, the East Asian cultures that have been assumed to be homogeneously collectivistic in previous psychological literature. Japanese and Korean participants rated a set of well-being and self-related scales. There were visible sample differences within culture by collection method (classroom vs. online) in relative degrees of selves and related constructs, possibly associated with generational differences. Other-focused relational self was greater in the Korean classroom sample than the Japanese counterpart, whereas no difference was found between the online samples. On the other hand, it was consistent between cultures that the two types of relational self showed different associations with social anxiety and self-esteem as expected, and that they predicted well-being in different ways. We discuss implications for the generational differences and their interactions with culture and the importance of separating the two aspects of relational self in the study of self and culture.